BUILDING EFFECTIVE DIGITAL INFRASTRUCTURE FOR TAXATION IN INDONESIA - Gunawan Widjaja (RADJA PUBLIKA, 2025)
This study discusses efforts to build effective digital infrastructure for taxation in Indonesia through a literature review. Digital transformation in the field of taxation, such as the implementation of e-Filing, e-Billing, and the Core Tax Administration System (Coretax), has brought significant changes in administrative efficiency and increased taxpayer compliance. However, the effectiveness of this digital infrastructure still faces various challenges, including the internet access gap, low digital and taxation literacy, and data security risks. In addition, regulations that are not yet fully adaptive to the development of the digital economy are also a separate obstacle. This study highlights the importance of equal access to technology, digital literacy education and training, strengthening cyber security, and updating responsive regulations as determining factors for the success of tax digitalisation. With the right strategies and cross-sector collaboration, Indonesia's digital tax infrastructure can become the foundation for a more equitable, efficient, and sustainable tax system.